47.9k views
1 vote
F^-1(4) when f(x) = 3x - 4/ 5

1 Answer

5 votes

Answer:
f^(-1)(4)=(8)/(5)

Explanation:

1. You need to find the Inverse function
f^(-1)(x):

- Given the function f(x):


f(x) = 3x - (4)/( 5)

- Rewrite it with
f(x)=y:


y= 3x - (4)/( 5)

- Now you must solve for "x":


y+(4)/( 5) = 3x\\\\(y+(4)/( 5))(3)=x\\\\x=(y)/(3)+(4)/(15)

- Now you must exchange the variables:


y=(x)/(3)+(4)/(15)

- Then:


f^(-1)(x)=(x)/(3)+(4)/(15)

2. Substitute
x=4 into the Inverse function and then evaluate:


f^(-1)(4)=((4))/(3)+(4)/(15)\\\\f^(-1)(4)=(8)/(5)

User Vitor Villar
by
6.1k points